Rotational Tillage Improves Photosynthesis of Winter Wheat during Reproductive Growth Stages in a Semiarid Region. (1st January 2013) - Hou, Xianqing; Li, Rong; Jia, Zhikuan; Han, Qingfang
Abstract : Tillage is important for soil water conservation and it affects crop growth, photosynthesis, and yield by adjusting soil water status in semiarid areas. A field study was conducted between 2007 and 2010 in the semiarid area of southern Ningxia, China, to determine the effects of rotational tillage practices on soil water status, flag leaves photosynthetic characteristics of late growth stage winter wheat ( Triticum aestivum L.), and grain yield. Three tillage treatments were tested: no‐tillage in Year 1, subsoiling in Year 2, and no‐tillage in Year 3 (NT/ST/NT, respectively); subsoiling in Year 1, no‐tillage in Year 2, and subsoiling in Year 3 (ST/NT/ST, respectively); and conventional tillage over Years 1 to 3 (CT). Compared with CT, the mean soil water storage during the wheat growing season was significantly ( p = 0.0305) higher at 0‐ to 2.0‐m depth with NT/ST/NT (+9.1%) and ST/NT/ST (+9.8%). The rotational tillage treatments significantly increased the net photosynthetic rate ( P N ), and transpiration rate ( E ) during the late growth stage. Greater intrinsic water use efficiency (WUEi ) was achieved with NT/ST/NT (+13.4%) and ST/NT/ST (+19.2%) at the filling stage when compared with CT. Meanwhile, rotational tillage treatments produced higher levels of maximal photochemical efficiency of photosystem II (PSII) ( F v / F m ) in darkness, actual photochemical efficiency of photosystem II (φ PSII) in light, and photosynthetic electron transport rate (ETR). Compared with CT, rotational tillage significantly increased wheat yields by 9.6% (NT/ST/NT) and 10.7% (ST/NT/ST). Overall, the results indicated that rotational tillage enhanced water conservation capacity, significantly improved crop photosynthetic characteristics and yield.